WHAT ECONOMIC THEORY SHOULD BE TAUGHT IF THE GOAL IS SUSTAINABLE DEVELOPMENT? - Egorov, Dmitry; Romanov, Valery; Yarmolich, Natalia; Egorova, Angela (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article is devoted to the topic of possible transformations in the paradigm of socio-economic development of modern world civilization, in the context of climate change. The purpose of the study: to identify what it would be desirable to change in textbooks on economics so that those who study, becoming managers and politicians, do not destroy the Earth’s biosphere by their actions. What in the economic mainstream underlies those pathological features of the world economy that lead all of humanity to the climatic apocalypse? At the level of theory, this is due to the extreme subjectivity of modern economic theory, which has taken the form of abandoning the category of “value”. The discussion of value is potentially of great practical importance: it is, in essence, a discussion of the legitimacy of the entire modern world financial and economic order. as the whole experience of world civilization shows, new ideas replace old ones when a new generation grows, for which these ideas are an organic part of their view of the world. Therefore, a change in the financial and economic paradigm should begin with changes in the textbooks of economics.